Peran Guru Pendidikan Agama Islam Di Era Digital - Sri Lestari; Jupriaman (Jurnal Zeniusi, 2024)
In today's digital era, access to information is increasingly easy and widespread, allowing students to access various educational and negative sources. Education faces a major challenge in remaining relevant to the progress of the times while maintaining Islamic religious values. Therefore, the role of Islamic Religious Education (PAI) teachers is very important in guiding students to minimize the negative impacts of the digital era. Education is a vital aspect of human development, influencing the formation of children's character and intellect. Based on Law No. 20 of 2003 on the NationalEducation System, education must develop students' spiritual potential, selfcontrol, and moral intelligence. PAI teachers must be able to utilize technology to design creative and interactive learning and supervise students'use of technology. Although digital technology offers many benefits, such as increased effectiveness and efficiency, it also poses challenges in accessingnegative content. This study uses a descriptive qualitative approach to describe the strategies of PAI teachers in instilling Islamic values in the digital era. The research findings show that integrating technology intoIslamic religious learning can increase students' motivation and access to information. Still, strict supervision is required to prevent the influence ofnegative content. Teachers must continue to improve their digital competencies and work with parents to create a learning environment that supports student character development and morals.